The Climate Changes in Banking Credit to The Financial Cycle During The Covid-19 Pandemic in Indonesia - Edwin Basmar; Carl M. Campbell-III; Erlin Basmar; Suhendra S. (Jurnal Manajemen Bisnis, 2022)
The Covid-19 Pandemic changed the banking credit climate that affected financial stability and Indonesia's economic growth, as measured using the development of the Ed Waves Index model through time series data from the Financial Statements of Bank Indonesia in 1950 – 2021, which found that the banking credit climate Pre-Covid-19 Pandemic was pressure between 1.4 Amplitude to 3.5 Amplitude and the financial cycle wave was pressure between 2.0 Amplitude to -0.3 Amplitude, while during Covid-19 Pandemic, the banking credit climate was pressure between -1.1 Amplitude to -2.1 Amplitude, while the financial cycle wave was pressure between - 2.0 Amplitude to -2.7 Amplitude, with different implications for financial stability and economic growth in Indonesia.